Electrical conductivity of silicate glasses with tetravalent cations substituting Si - Braunger, M. L. [UNESP]; Escanhoela, C. A.; Fier, I. [UNESP]; Walmsley, L. [UNESP]; Ziemath, E. C. [UNESP] (Elsevier B.V., 2012)
The effects of substituting Si by M4+ cations in soda-lime silica glasses were analyzed by impedance spectroscopy in the frequency range of 1 Hz-1 MHz. The glass composition was (mol%) 22Na(2)O center dot 8CaO center dot 65SiO(2)center dot 5MO(2), M = Si, Ti, Ge, Zr, Sn, and Ce. Although the Na+ concentration in the glasses is constant, the Zr-containing glass exhibits the highest dc conductivity and the lowest activation energy, while the Ce-containing glass exhibits the lowest conductivity. The activation energies obtained experimentally agree with those obtained by a theoretical equation proposed by Anderson and Stuart. The differences in electrical conductivity presented by the several M-containing glasses are attributed to the effect that the M4+ ion has on the mobility of the diffusing Na+ ion. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Silicate glass; Impedance spectroscopy; Electrical conductivity